Does Corruption Corrupt? The Behavioral Effects of Mediated Exposure to Corruption. (10th December 2021) - Waismel-Manor, Israel; Moy, Patricia; Neumann, Rico; Shechnick, Moran
Abstract: Corruption is a complex, widespread phenomenon with harmful economic and societal effects. Drawing upon theories in social psychology, political science, and communication, this study examines the direct and joint effects of mediated exposure to grand corruption and the presence of monetary incentives on people's likelihood to engage in dishonest behavior. In a 2 × 2 factorial design ( N = 404), half of all participants were exposed to a newscast about political corruption and one half was offered a reward for correctly answering questions about the newscast. Findings suggest that incentivizing was highly effective in predicting chances of cheating while news exposure to corruption was not. The data also indicate cheating is more common among certain sociodemographic groups.